The Impact of Tsunami on Seagrass Ecosystem in Tanjung Lesung, Banten, Indonesia - Muta Ali Khalifa; Ani Rahmawati; Forcep Rio Indaryanto; Luky Adrianto; Syamsul Bahri Agus; Fery Kurniawan; Aldi Agus Setiawan; Desy Aryani; Agustin Rustam (Journal Omni-Akuatika, 2020)
The Sunda Strait Tsunami (end of 2018) has an impact on the seagrass ecosystem in Tanjung Lesung. This paper described the seagrass ecosystem’s changes after the tsunami disaster. Sentinel-2 satellite image processing in 2018 and 2019 was used to see changes in the seagrass area. The field data were collected from May–July 2019, including the types of seagrass ecosystems based on data seagrass existence, density and biomass. Then, the seagrass sample was analyzed biomass after the tsunami disaster. The results showed that the data from 2018 – 2019 showed decreased seagrass area from 105.86 to 77.07 ha. Seagrass density dropped quite dramatically, and the species of Halodule uninervis was no longer found. The ratio of after tsunami BG/AbG dry biomass has doubled compared to before the tsunami, which indicates the seagrass's lower biomass is higher than the upper part allegedly due to tsunami impacts. Based on the results obtained, it can be concluded that the seagrass ecosystems changed and disrupted by the tsunami. Keywords: Seagrass, Tanjung Lesung, Tsunami, Sentinel-2